Efektivitas Mediasi Online dalam Perkara Perceraian di Pengadilan Agama Samarinda - Chairina; Lilik Andar Yuni (Bulletin of Community Engagement, 2024)
Online mediation in divorce cases at the Samarinda Religious Court has factors that make the mediation carried out online, therefore there is an agreement between the two parties and the mediator is the person who helps with the mediation. The factor is the difference in area between the plaintiff and the defendant. The purpose of online mediation is first, to find out the application of online mediation in divorce cases at the Samarinda Religious Court. Second, to determine the effectiveness of online mediation in divorce cases at the Samarinda Religious Court. This research uses empirical-normative legal research methods with qualitative analysis. The data source used is primary data from the statements of 5 informants at the research location. And secondary data was obtained from primary legal materials from Perma No. 1 of 2016. The results of the first research, there were obstacles because the parties did not comply with the regulations regarding dishonesty of the parties, so that online mediation was not carried out well. Second, measuring out of 10 cases that carried out online mediation, only 2 cases were successful in online mediation,